The impact of SMEs' lending and credit guarantee on bank efficiency in South Korea - Lien-Wen Liang; Bor-yi Huang; Chih-Feng Liao; Yu-Ting Gao (Review of Development Finance, 2017)
This study examines how small and medium-size enterprises' (SMEs') lending and credit guarantee affect Korean banks' efficiency, by employing the stochastic frontier approach on 14 banks over the period 2001-2010. When lending increases to SMEs, the findings indicate that banks' cost efficiency decreases due to information asymmetry. However, the increased proportion of credit guarantee can improve their cost efficiency. This proves that South Korea's credit guarantee system can indeed share SMEs' credit risk of lending in order to help raise bank efficiency.
Keywords: C33; G21; G30; 650; SME lending; Credit guarantee; Bank efficiency